Policy risk, strategic decisions and contagion effects: Firm‐specific considerations - Blake, Daniel J.; Moschieri, Caterina (Strategic Management Journal, 2017)
Research summary : In this article, we investigate the firm‐specific environment and its impact on firm strategy focusing on adverse changes in the policy environment and their effect on divestitures. We argue that experiencing a negative change in the firm‐specific policy environment causes firms to reassess their exposure to policy risk and their ability to manage their policy environment, making them more likely to divest. Operationalizing negative shifts in the firm‐specific policy environment through formal policy disputes between firms and governments, we find that following a dispute, firms are more likely to divest both in the country where the dispute occurs and in other countries in the same region. However, the impact of disputes on divestitures is firm specific, applying only to firms directly involved in a dispute . Managerial summary : What is the impact of change in the firm‐specific environment on firm strategy? We argue that when firms directly experience a negative change in their policy environment that is specific to them, they negatively reassess their exposure to policy risk and their ability to manage their policy environment, which makes them more likely to undertake a divestiture. We analyze formal disputes between firms and governments that arise from adverse changes in policy and find that, following a dispute, firms are more likely to divest in the country where the dispute occurs and in other countries in the same region. However, the impact of disputes on divestitures is firm specific as it applies only to firms directly involved in a dispute . Copyright © 2016 John Wiley & Sons, Ltd.